Zinc-free primer, shipping container, powder protective coating and construction process thereof

By using zinc-free high-solid oil-containing paint and non-metal conductive materials in container protective coatings, a multi-layer coating structure is formed, which solves the pollution and erosion problems caused by traditional zinc-rich primers, and achieves a more environmentally friendly and more Durable container protection.

CN119489029APending Publication Date: 2025-02-21CIMC CONTAINERS HLDG +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411085717.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-16
Filing Date
2024-08-08
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The use of water-based paint in traditional container protection causes pollution problems of a large number of organic solvents and wastewater, and zinc-rich primer has problems with VOC emissions and corrosion and spreading.

Method used

Use zinc-free high-solid oil-containing paint and non-metal conductive materials to replace metal zinc to form a three-layer coating structure, including A1, A2 and A3, as well as B1, B2 and B3, through rolling and spraying Construction is carried out by process.

Benefits of technology

It reduces the erosion phenomenon, extends the service life of the container, reduces VOC emissions and sewage treatment problems, and has significant environmental protection effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119489029A_ABST
    Figure CN119489029A_ABST
Patent Text Reader

Abstract

The invention provides a zinc-free primer, a shipping container, a powder protective coating and a construction process thereof, and develops a zinc-free pretreatment primer. High-solid-content oily paint is adopted, and a non-metal conductive material is adopted to replace metal zinc. Compared with the prior art, the metal zinc is not contained, so that the corrosion expansion phenomenon can be reduced. Due to the fact that the non-metal conductive material and the high-solid-oil paint are mixed more sufficiently, the first layer can be thinner, and meanwhile the corrosion resistance of the first layer is better. And meanwhile, the adhesive force of the powder is better, and subsequent spraying is more facilitated. According to the construction process disclosed by the invention, in order to avoid the problem of discharge of sewage after degreasing pretreatment of acid, alkali and the like, the pretreatment adopts a treatment mode of laser and fine sanding, so that the generation of discharged dust and noise can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a zinc-free primer, a shipping container, a powder protective coating and a construction process thereof. Background Art

[0002] Traditional container protection uses water-based paint, which consumes a large amount of organic solvents and produces a large amount of wastewater and waste residue. Pollution problems have always plagued the industry.

[0003] In the container field, Jingyuan has successfully developed powder coatings for containers in 2022. After the official announcement in August 2022, it has produced nearly 30,000 TEU containers and formed a group standard. At present, the applicant uses a protective coating system for container cold-rolled steel plates, in which the first layer is a zinc-rich primer with a thickness of more than 35 microns, followed by spraying of the primer and topcoat.

[0004] Specifically, when using metal plates, such as cold-rolled steel plates to produce containers, there is a small amount of oil on the surface of the cold-rolled steel plates due to process reasons when they leave the factory, so the cold-rolled steel plates must be pre-treated before cold working. First, the steel plate surface is degreased (acid or alkali degreasing), then cleaned, dried (air-dried or hot air), shot blasted, and pre-coated with zinc-rich primer. After the pre-treatment is completed, it will enter the cold working process (punching, shearing and pressing), steel structure assembly welding, and the welds will be shot blasted before the whole box is painted (including painting, powder spraying, etc.).

[0005] In actual use, the containers produced by the above spraying method have various performances that surpass those produced by the previous water-based paint method. However, the above cold-rolled steel plate cold working pre-treatment process has the following problems: 1. There is a problem of sewage treatment; 2. The zinc-rich primer is an oil-based paint (non-aqueous) and has the problem of VOC emissions. The above two points bring the hidden danger of not meeting environmental protection standards. At the same time, the applicant found that for shipping containers with high corrosion resistance requirements, once corrosion occurs, the corrosion expansion is serious.

[0006] Therefore, a new coating system and coating process are needed to solve the above problems. Summary of the invention

[0007] The present invention is proposed to alleviate or solve at least one aspect or at least one point of the above problems.

[0008] The present invention provides a powder protective coating for a shipping container, wherein the container comprises an inner surface of the container and an outer surface of the container; at least a portion of the container is processed from a metal sheet;

[0009] in:

[0010] The metal sheet forming the inner surface of the container includes at least three layers of coating structure: A1 layer, A2 layer, and A3 layer. The material of A1 layer includes: high-solid oil-based paint, non-metallic conductive material; A1 layer does not contain metal zinc; the material of A2 layer is epoxy powder; the material of A3 layer is epoxy powder;

[0011] And / or, the metal sheet forming the outside of the container comprises at least: a three-layer coating structure of B1 layer, B2 layer, and B3 layer; the material of B1 layer comprises: high-solid oil-based paint, non-metallic conductive material; B1 layer does not contain metallic zinc; the material of B2 layer is epoxy powder; the material of B3 layer is polyester powder.

[0012] Preferably, the A1 layer does not contain zinc; and the B1 layer does not contain zinc.

[0013] Preferably, the A1 layer is formed by roll coating before the metal sheet is formed into a container; the A2 and A3 layers are formed by spraying after the container body is formed; and / or the B1 layer is formed by roll coating before the metal sheet is formed into a container; the B2 and B3 layers are formed by spraying after the container body is formed.

[0014] Preferably, the thickness of the A1 layer is less than the thickness of the A2 and A3 layers; and / or the thickness of the B1 layer is less than the thickness of the B2 and B3 layers; preferably, the thickness of the A1 layer is less than 20 microns, more preferably less than 12 microns.

[0015] Preferably, the thickness of the A1 layer is 8-12 microns, the thickness of the A2 layer is 37-43 microns, and the thickness of the A3 layer is 38-43 microns;

[0016] And / or, the thickness of the B1 layer is 8-12 microns, the thickness of the B2 layer is 37-43 microns, and the thickness of the B3 layer is 44-46 microns.

[0017] Preferably, the solid content ratio of the high-solid oily paint in the A1 layer is not less than 60%, and the content of the non-metallic conductive material ranges from 0.5% to 10% of the weight of the high-solid oily paint;

[0018] And / or, the solid content of the high-solid oily paint in the B1 layer is not less than 60%, and the content of the non-metallic conductive material is in the range of 0.5%-10% of the weight of the high-solid oily paint.

[0019] Preferably, the zinc content in the A1 and B1 layers is zero, and the thickness of the A1 layer is substantially the same as that of the B1 layer.

[0020] Preferably, the non-metallic conductive material in the A1 and B1 layers is graphite, and the graphite content is approximately 2%.

[0021] Preferably, the solid content of the high-solid oily paint in the A1 and B1 layers is 70%, and the content of the non-metallic conductive material is in the range of 5% of the weight of the high-solid oily paint.

[0022] In addition, the present invention also provides a construction process for a protective coating of a container, comprising the following steps:

[0023] Derusting and / or sanding metal sheets;

[0024] With hot coating, the coating or the plate is heated before coating the A1 layer and the B1 layer;

[0025] Drying or air drying, wherein the air drying uses hot air;

[0026] Processing and welding metal sheets to form a box;

[0027] Sandblast the welds of the entire box;

[0028] A2 layer and B2 layer are sprayed; A3 layer and B3 layer are sprayed;

[0029] Solidify and cool.

[0030] Preferably, when hot air is used for air drying, the temperature of the plate having a thickness of 4 mm or more after being heated by hot air is not less than 85°C.

[0031] Preferably, before hot roller coating, the process also includes mixing the high-solid oily paint and the non-metallic conductive material evenly.

[0032] Preferably, after the metal sheet is sandblasted, its surface roughness is between 15-35 microns.

[0033] The present invention also provides a shipping container, comprising any one of the protective coatings described above; or, using the construction process described above.

[0034] Preferably, the materials forming the A1 layer and the B1 layer include, by mass percentage, 25-30% of modified epoxy resin, 10-15% of anti-rust pigment, 3-5% of cyclohexanone, 8-10% of xylene, 3-6% of n-butanol, 8-20% of curing agent, and 0.5-10% of non-metallic conductive material, with the remainder being pigments and fillers.

[0035] Preferably, the non-metallic conductive material includes at least one of graphite, graphene and conductive mica.

[0036] Preferably, in terms of mass percentage, the epoxy powders of A2 and B2 include: 25-50% polyester resin, 22-45% epoxy resin, 1-10% phenolic curing agent, 0.1-2.4% accelerator, 0.5-2% leveling agent, 0.1-2% deaerator, 5-30% composite filler and 0.2-2% toughening agent, and the rest are pigments and fillers.

[0037] Preferably, the polyester resin has an acid value of 34 to 76 mgKOH / g and a viscosity of 3000 to 6000 mPa.s; and / or,

[0038] The epoxy value of the epoxy resin is 0.090-0.165 eq / 100 g, and the softening point is 87-105° C.

[0039] Preferably, in terms of mass percentage, the epoxy powder of A3 includes 30-60% polyester resin, 20-36% epoxy resin, 0.5-1% leveling agent, 0.1-1% defoaming agent, 0.2-2% antioxidant 0.2-2% and 0.5-3% toughening agent, and the rest is pigment and filler.

[0040] Preferably, the polyester resin has an acid value of 34 to 76 mgKOH / g and a viscosity of 3000 to 6000 mPa.s; and / or,

[0041] The epoxy value of the epoxy resin is 0.090-0.165 eq / 100 g, and the softening point is 87-105° C.

[0042] Preferably, in terms of mass percentage, the polyester powder of B3 includes 30-45% of high weather resistant polyester resin, 22-35% of super weather resistant polyester resin, 0-3.5% of triglycidyl isocyanurate, 0-2.5% of hydroxyalkylamide, 14-24% of blocked polyisocyanate, 0.5-1.5% of leveling agent, 0.1-3% of accelerator, 0.1-1% of defoamer, 0.5-3.2% of toughening agent, 0.2-2% of antioxidant and 2-25% of composite filler, and the rest is color filler.

[0043] Preferably, the acid value of the highly weather-resistant polyester is 29-34 mgKOH / g, and the viscosity is 4500-6000 mPa﹒ s;

[0044] The super weather-resistant polyester has a hydroxyl value of 100-120 mgKOH / g and a viscosity of 3200-4200 mPa﹒s.

[0045] The present invention also provides a zinc-free primer for use in containers, which comprises, by mass percentage, 25-30% of a modified epoxy resin, 10-15% of an anti-rust pigment, 3-5% of cyclohexanone, 8-10% of xylene, 3-6% of n-butanol, 8-20% of a curing agent, and 0.5-10% of a non-metallic conductive material, with the remainder being pigments and fillers.

[0046] Preferably, the non-metallic conductive material includes at least one of graphite, graphene and conductive mica.

[0047] The present invention further improves and optimizes the powder coating system and develops a zinc-free pre-treatment primer. A high-solid oily paint is used, and non-metallic conductive materials are used instead of metallic zinc. Through the above arrangement, compared with the prior art, the corrosion expansion phenomenon can be reduced because the metallic zinc is not contained.

[0048] Since the first layer uses high-solid oily paint and non-metallic conductive materials, and non-metallic conductive materials are used instead of metal zinc, the conductive performance can be guaranteed, which is beneficial to the subsequent spraying. At the same time, the expansion corrosion phenomenon can be reduced. At the same time, since the non-metallic conductive materials and high-solid oily paint are mixed more fully, the first layer can be made thinner, and at the same time, its corrosion resistance is better. Since the A1 layer is formed before the container is assembled, it is necessary to ensure weldability by welding and assembling to form the container. Adding non-metallic conductive materials to improve the conductivity of the A1 layer avoids affecting welding.

[0049] Since it does not contain metal materials, its powder has better adhesion and is more conducive to subsequent spraying. Through actual verification, the zinc-free pre-treatment primer fully meets the requirements of rust prevention between processes. The zinc-free pre-treatment primer has better adhesion to the powder, and its corrosion expansion is better than that of water-based paint. Its welding performance is consistent with that of zinc-rich primer. At the same time, the cost of zinc-free pre-treatment primer is lower than that of zinc-rich primer, and its weight is also lighter.

[0050] The construction process of the present invention adopts laser rust removal in pre-treatment to avoid the discharge of sewage, adopts high-solid paint to effectively reduce VOC emissions, and compared with the prior art, its thickness is greatly reduced, saving materials and having good environmental protection effects.

[0051] The present invention breaks the tradition of using zinc-rich primer in the current container field, and creatively uses zinc-free primer, so that the A1 layer and the B1 layer do not contain zinc, and uses non-metallic conductive materials to ensure the conductive performance. Therefore, when corrosion occurs, there is no zinc salt generation phenomenon, thereby avoiding the separation between the bottom layer and the substrate caused by volume expansion, thereby reducing the corrosion expansion phenomenon and extending the service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 The anti-corrosion performance experimental sample of Example 1 of the present invention.

[0053] Figure 2 The anti-corrosion performance experimental sample of Example 2 of the present invention.

[0054] Figure 3 The anti-corrosion performance experimental sample of Example 2 of the present invention.

[0055] Figure 4 The anti-corrosion performance experimental sample of comparative example 1.

[0056] Figure 5 This is the anti-corrosion performance test sample of Example 5 of the present invention.

[0057] Figure 6 This is the anti-corrosion performance test sample of Example 6 of the present invention.

[0058] Figure 7 This is the anti-corrosion performance test sample of Example 7 of the present invention.

[0059] Figure 8 This is the anti-corrosion performance experimental sample of Example 11 of the present invention.

[0060] Fig. 9 This is the anti-corrosion performance experimental sample of Example 12 of the present invention.

[0061] Fig.10 This is the anti-corrosion performance experimental sample of Example 13 of the present invention.

[0062] Fig.11 This is the anti-corrosion performance test sample of Example 2.

[0063] Fig.12 This is the anti-corrosion performance test sample of Example 3. DETAILED DESCRIPTION

[0064] The following description of the embodiments of the present invention with reference to the accompanying drawings is intended to explain the overall inventive concept of the present invention, and should not be construed as a limitation of the present invention. In the present invention, the same reference numerals represent the same or similar components.

[0065] The features described herein can be implemented in different forms and should not be construed as being limited to the examples described herein. Rather, the examples described herein have been provided to illustrate only some of the many possible ways to implement the methods, devices, and / or systems described herein, which will be clear after understanding the disclosure of the present invention.

[0066] Although terms such as "first", "second", and "third" may be used herein to describe various members, components, regions, layers, or portions, these members, components, regions, layers, or portions should not be limited by these terms. Instead, these terms are only used to distinguish one member, component, region, layer, or portion from another member, component, region, layer, or portion.

[0067] The terms used herein are only used to describe various examples and are not intended to limit the disclosure. Unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. The terms "comprise", "include" and "have" indicate the presence of the described features, quantities, operations, components, elements and / or combinations thereof, but do not exclude the presence or addition of one or more other features, quantities, operations, components, elements and / or combinations thereof.

[0068] In order to enable those skilled in the art to use the contents of the present invention, the following exemplary embodiments may be provided in combination with specific application scenarios, specific systems, parameters of devices and components, and specific connection methods. However, for those skilled in the art, these embodiments are only examples, and the general principles defined herein may be applied to other embodiments and application scenarios without departing from the spirit and scope of the present invention.

[0069] The invention provides a powder protective coating for a shipping container, wherein the container comprises an inner surface of the container and an outer surface of the container. At least part of the container is processed from a metal sheet.

[0070] Wherein: the metal plate forming the inner surface of the container at least comprises: A1 layer, A2 layer, A3 layer three-layer coating structure: the material of A1 layer comprises: high solid oil paint, non-metallic conductive material; A1 layer does not contain metal zinc; the material of A2 layer is epoxy powder; the material of A3 layer is epoxy powder;

[0071] And / or, the metal sheet forming the outside of the container comprises at least: a three-layer coating structure of B1 layer, B2 layer, and B3 layer; the material of B1 layer comprises: high-solid oil-based paint, non-metallic conductive material; B1 layer does not contain metallic zinc; the material of B2 layer is epoxy powder; the material of B3 layer is polyester powder.

[0072] It should be noted that the existing container manufacturing companies are in an upstream and downstream supply relationship with primer suppliers and powder suppliers, and the three are generally different manufacturers. In the current existing technology, containers generally use zinc-rich primer as the base coating, and powder suppliers basically do not make improvements or research on zinc-rich primers for containers. The main function of the primer is to provide temporary protection for the intermediate plate used in container production before the powder coating is applied. The anti-corrosion performance of container terminal products basically relies on the middle layer paint and topcoat to achieve anti-corrosion protection. Therefore, when corrosion problems occur in container terminal products, container manufacturers generally believe that the corrosion is caused by the middle layer paint or topcoat. Therefore, when facing the overall coating solution formed by powder coating and container zinc-rich primer, it is difficult for technical personnel in this field to find that it is the problem of zinc-rich primer composition that affects the anti-corrosion ability of powder coating, and they will only think that there is a problem with the powder coating itself.

[0073] The inventor of the present application has made a creative discovery: After research and analysis, the applicant has found that the reason why the current shipping containers are severely corroded is that they use zinc-rich primers. When corrosion occurs, a large amount of zinc powder in the zinc-rich primer changes to form zinc salts, and the production of zinc salts causes the volume of the primer to expand. The single powder coating formed on the box body is extremely dense and cannot accommodate the volume expansion of the zinc salts, which causes the powder coating to separate from the box body, resulting in the phenomenon of the entire powder coating "peeling off". And as the zinc powder continues to corrode, the "peeling off" will continue to extend.

[0074] Zinc powder reacts with chloride ions in chloride to form zinc salt zinc chloride, that is, zinc ions.

[0075] Zinc ions continue to react in an environment of oxygen, water and carbon dioxide to form basic zinc carbonate. Basic zinc carbonate is a powdery substance that is insoluble in water and alcohol.

[0076] The specific reaction formula is as follows:

[0077] Zn+2Cl - →ZnCl2,

[0078] Zn 2+ +O2+H2O+CO2→ZnCO3·ZN(OH)2.

[0079] At the same time, the applicant has found that the zinc-rich primer surface coating contains zinc, and compared with the zinc-free primer, there is a risk of quality degradation when combined with the subsequent powder coating. Therefore, the present invention provides an A1 layer and / or B1 layer that does not contain zinc, thereby eliminating the generation of zinc salts and reducing the corrosion phenomenon.

[0080] The invention provides a zinc-free primer applied to a container. The zinc-free primer is a material for forming an A1 layer and a B1 layer.

[0081] Specifically, according to mass percentage, the zinc-free primer includes 25-30% modified epoxy resin, 10-15% anti-rust pigment, 3-5% cyclohexanone, 8-10% xylene, 3-6% n-butanol, 8-20% curing agent, and 0.5-10% non-metallic conductive material, and the rest is pigment filler.

[0082] The materials forming the A1 layer and the B1 layer include, by mass percentage, 25-30% of modified epoxy resin, 10-15% of anti-rust pigment, 3-5% of cyclohexanone, 8-10% of xylene, 3-6% of n-butanol, 8-20% of curing agent, and 0.5-10% of non-metallic conductive material, and the rest are pigments and fillers.

[0083] The modified epoxy resin can be an isocyanate modified epoxy resin, a silicone acrylic modified epoxy resin, a dimer acid modified epoxy resin, an acrylic modified epoxy resin, a low polymerization degree modified epoxy resin, ZJ-101 epoxy modified acrylic resin produced by Suzhou Shengjia Resin Co., Ltd., etc.

[0084] The curing agent includes at least one of polyamide 650, modified polyamide, isocyanate trimer and triethylenetetramine.

[0085] The anti-rust pigment includes at least one of aluminum tripolyphosphate, zinc phosphate, zinc oxide, aluminum phosphate, zinc molybdate, and aluminum oxide.

[0086] The pigments and fillers of the A1 layer and the B1 layer include, but are not limited to, at least one of titanium dioxide, iron oxide red, iron oxide yellow, ultramarine, phthalocyanine blue, phthalocyanine green, medium chrome yellow, DPP red, permanent red, permanent violet, barium sulfate, silica powder, wollastonite, mica powder, glass powder, quartz powder, carbon black, and titanium dioxide.

[0087] The non-metallic conductive material includes at least one of graphite, graphene or conductive mica.

[0088] According to mass percentage, the epoxy powder of layer A2 and layer B2 includes 25-50% polyester resin, 22-45% epoxy resin, 1-10% phenolic curing agent, 0.1-2.4% accelerator, 0.5-2% leveling agent, 0.1-2% deaerator, 5-30% composite filler and 0.2-2% toughening agent, and the rest is pigment filler.

[0089] The acid value of the polyester resin of the A2 layer and the B2 layer is 34 to 76 mgKOH / g, and the viscosity is 3000 to 6000 mPa﹒ s.

[0090] The epoxy value of the epoxy resin of the A2 layer and the B2 layer is 0.090 to 0.165 eq / 100 g, and the softening point is 87 to 105°C.

[0091] The phenolic curing agent can be 969H06 phenolic curing agent produced by Daqing Qinglu Langrun Technology Co., Ltd. or other existing phenolic curing agents.

[0092] The accelerators of the A2 layer and the B2 layer include at least one of imidazoline, colorless cobalt, methyldiethanolamine, aminophenol, and 2,4,6-tris(dimethylaminomethyl)phenol.

[0093] The leveling agent of the A2 layer and the B2 layer includes at least one of polyacrylic acid, acrylic acid ester polymer, polyether polyester modified organic siloxane, acrylic acid, fluorine modified acrylic acid, phosphate modified acrylic acid, acrylic resin, urea formaldehyde resin and melamine formaldehyde resin.

[0094] The degassing agent of the A2 layer and the B2 layer includes at least one of benzoyl ketone and stearic acid.

[0095] The composite fillers of the A2 layer and the B2 layer include at least one of aluminum oxide, boron nitride, zinc oxide, mica powder and silicon dioxide.

[0096] The toughening agent of the A2 layer and the B2 layer includes at least one of nano silicon dioxide, methyl methacrylate-butadiene-styrene terpolymer, dimethyl phthalate, diethyl phthalate, dibutyl phthalate, triethyl phosphate and tributyl phosphate.

[0097] The pigments and fillers of the A2 layer and the B2 layer include, but are not limited to, at least one of titanium dioxide, iron oxide red, iron oxide yellow, ultramarine, phthalocyanine blue, phthalocyanine green, medium chrome yellow, DPP red, permanent red, permanent violet, barium sulfate, silica powder, wollastonite, mica powder, glass powder, quartz powder, carbon black, and titanium dioxide.

[0098] According to mass percentage, the epoxy powder of the A3 layer includes 30-60% polyester resin, 20-36% epoxy resin, 0.5-1% leveling agent, 0.1-1% defoaming agent, 0.2-2% antioxidant and 0.5-3% toughening agent, and the rest is pigment and filler.

[0099] The acid value of the polyester resin of the A3 layer is 34 to 76 mgKOH / g, and the viscosity is 3000 to 6000 mPa﹒s.

[0100] The epoxy value of the epoxy resin of the A3 layer is 0.090 to 0.165 eq / 100 g, and the softening point is 87 to 105°C.

[0101] The leveling agent of the A3 layer includes at least one of polyacrylic acid, acrylic acid ester polymer, polyether polyester modified organic siloxane, acrylic acid, fluorine modified acrylic acid, phosphate modified acrylic acid, acrylic resin, urea formaldehyde resin and melamine formaldehyde resin.

[0102] The defoamer of the A3 layer includes at least one of TEGO Foamex 825, TEGO Foamex 810, BYK-028, BYK-024, TEGO-902W, defoamer NXZ, BYK-022 defoamer of BYK Chemical, polydimethylsiloxane defoamer, AKN-3324, benzoin, BYK-066N and BYK085.

[0103] The antioxidant of the A3 layer includes at least one of B215 composite antioxidant, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 2,6-tert-butyl-4-methylphenol, bis(3,5-tert-butyl-4-hydroxyphenyl) sulfide and BASF antioxidant 1010.

[0104] The toughening agent of the A3 layer includes at least one of nano-silicon dioxide, methyl methacrylate-butadiene-styrene terpolymer, dimethyl phthalate, diethyl phthalate, dibutyl phthalate, triethyl phosphate, and tributyl phosphate.

[0105] The pigments and fillers of the A3 layer include, but are not limited to, at least one of titanium dioxide, iron oxide red, iron oxide yellow, ultramarine, phthalocyanine blue, phthalocyanine green, medium chrome yellow, DPP red, permanent red, permanent violet, barium sulfate, silica powder, wollastonite, mica powder, glass powder, quartz powder, carbon black, and titanium dioxide.

[0106] According to mass percentage, the polyester powder of layer B3 includes 30-45% of high weather-resistant polyester resin, 22-35% of super weather-resistant polyester resin, 0-3.5% of triglycidyl isocyanurate, 0-2.5% of hydroxyalkylamide, 14-24% of blocked polyisocyanate, 0.5-1.5% of leveling agent, 0.1-3% of accelerator, 0.1-1% of defoaming agent, 0.5-3.2% of toughening agent, 0.2-2% of antioxidant and 2-25% of composite filler, and the rest is color filler.

[0107] The acid value of the high weather-resistant polyester of the B3 layer is 29-34 mgKOH / g, and the viscosity is 4500-6000 mPa﹒ s.

[0108] The hydroxyl value of super weather-resistant polyester is 100-120 mgKOH / g, and the viscosity is 3200-4200 mPa﹒s.

[0109] Triglycidyl isocyanurate is referred to as TGIC.

[0110] Hydroxyalkylamide is referred to as HAA.

[0111] The blocked polyisocyanate may be any one or more of EVONIK's brands B1400, BF1540 and BF1320.

[0112] The leveling agent of the B3 layer includes at least one of polyacrylic acid, acrylic acid ester polymer, polyether polyester modified organic siloxane, acrylic acid, fluorine modified acrylic acid, phosphate modified acrylic acid, acrylic resin, urea formaldehyde resin and melamine formaldehyde resin.

[0113] The accelerator of the B3 layer includes at least one of imidazoline, colorless cobalt, methyldiethanolamine, aminophenol, and 2,4,6-tris(dimethylaminomethyl)phenol.

[0114] The defoamer of the B3 layer includes at least one of TEGO Foamex 825, TEGO Foamex 810, BYK-028, BYK-024, TEGO-902W, defoamer NXZ, BYK-022 defoamer of BYK Chemical, polydimethylsiloxane defoamer, AKN-3324, benzoin, BYK-066N and BYK085.

[0115] The toughening agent of the B3 layer includes at least one of nano silicon dioxide, methyl methacrylate-butadiene-styrene terpolymer, dimethyl phthalate, diethyl phthalate, dibutyl phthalate, triethyl phosphate and tributyl phosphate.

[0116] The antioxidants in the B3 layer include at least one of B215 composite antioxidant, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 2,6-tert-butyl-4-methylphenol, bis(3,5-tert-butyl-4-hydroxyphenyl) sulfide and BASF antioxidant 1010.

[0117] The composite filler of the B3 layer includes at least one of aluminum oxide, boron nitride, zinc oxide, mica powder and silicon dioxide.

[0118] The color and filler of the B3 layer are inorganic pigments and fillers, including but not limited to at least one of titanium dioxide, iron oxide red, iron oxide yellow, ultramarine, phthalocyanine blue, phthalocyanine green, medium chrome yellow, DPP red, permanent red, permanent violet, barium sulfate, silica powder, wollastonite, mica powder, glass powder, quartz powder, carbon black, and titanium dioxide.

[0119] In the entire protective layer, the epoxy group of the A1 layer can react with the polyester carboxyl group in the A2 layer to connect the A1 and A2 layers through chemical bonding. The carboxyl group of the polyester resin in the A2 layer can react with the epoxy group in the A3 layer to connect the A2 and A3 layers through chemical bonding.

[0120] The epoxy group in the B1 layer can react with the polyester carboxyl group in the B2 layer to connect the B1 and B2 layers through chemical bonding. The carboxyl group of the polyester resin in the B2 layer can react with the curing agent in the B3 layer to connect the B2 and B3 layers through chemical bonding.

[0121] Therefore, the interlayer bonding force of the entire protective coating is strong. In the adhesion pull-off test, the breaking strength reaches more than 10Mpa, and the entire protective coating partially falls off from the substrate together, without the phenomenon of interlayer shedding.

[0122] After the A1 layer and the B1 layer are formed on the substrate, they protect the substrate through physical isolation and can meet the function of temporary protection of the substrate. The interior of the container product is protected from corrosion by the A2 layer and the A3 layer, and the exterior of the container is protected from corrosion by the B2 layer and the B3 layer.

[0123] The A1 layer is formed by coating the metal sheet before it is formed into a container, and the A2 and A3 layers are formed by spraying after the container body is formed.

[0124] And / or, the B1 layer is formed by coating the metal sheet before forming the container, and the B2 and B3 layers are formed by spraying after forming the container body.

[0125] The thickness of the A1 layer is smaller than that of the A2 and A3 layers.

[0126] Preferably, the thickness of the A1 layer is 8-12 microns. When the thickness is less than 8 microns, the corrosion expansion performance is poor. When the thickness is greater than 12 microns, the cost is increased. The thickness of the A2 layer is 37-43 microns, and the thickness of the A3 layer is 38-43 microns. When the thickness of the A2 layer is less than 37 microns, the corrosion resistance is poor. When the thickness of the A2 layer is greater than 43 microns, the cost is increased. When the thickness of the A3 layer is less than 38 microns, the corrosion resistance is poor. When the thickness of the A3 layer is greater than 43 microns, the cost is increased.

[0127] And / or, the thickness of the B1 layer is smaller than the thickness of the B2 and B3 layers.

[0128] Preferably, the thickness of the B1 layer is 8-12 microns, the thickness of the B2 layer is 37-43 microns, and the thickness of the B3 layer is 44-46 microns.

[0129] The solid content ratio of the high-solid oily paint in the A1 layer is not less than 60%, and the content of the non-metallic conductive material ranges from 0.5% to 10% of the weight of the high-solid oily paint.

[0130] And / or, the solid content of the high-solid oily paint in the B1 layer is not less than 60%, and the content of the non-metallic conductive material is in the range of 0.5%-10% of the weight of the high-solid oily paint.

[0131] The non-metallic conductive material in the A1 and B1 layers is graphite, and the content of graphite is approximately 2%.

[0132] The solid content ratio of the high-solid oily paint in the A1 and B1 layers is 70%, and the content of the non-metallic conductive material is in the range of 5% of the weight of the high-solid oily paint.

[0133] The present invention also provides a construction method for a protective coating for engineering equipment, comprising the following steps:

[0134] S1. Laser rust removal and / or sandblasting of metal sheets.

[0135] S2, with hot coating, after heating the paint or the plate, apply the A1 layer and B1 layer.

[0136] Specifically, when the thickness of the metal sheet is greater than 4 mm, the metal sheet is heated to a temperature greater than or equal to 85° C.

[0137] When the thickness of the metal sheet is less than 4mm, it is usually heated to 85℃.

[0138] The temperature of the heated coating was 40°C.

[0139] S3, drying or air drying, wherein the air drying uses hot air.

[0140] S4. Processing and welding the metal plates to form a box.

[0141] S5. Sandblast the welds of the entire box.

[0142] S6, A2 layer, and B2 layer are sprayed; A3 layer and B3 layer are sprayed.

[0143] S7, solidification and cooling.

[0144] The present invention also provides a shipping container, comprising the above-mentioned protective coating; or, adopting the above-mentioned construction process.

[0145] The above-mentioned protective coating is introduced below through various embodiments.

[0146] Embodiment 1:

[0147] Step 1: Derust the metal sheet and perform fine sandblasting to a surface roughness of 15-35 microns; rust removal is performed using laser rust removal, which can avoid pollution compared to existing rust removal methods.

[0148] Step 2: Roll coating, use high-solid oily paint to apply the first layer of coating to the metal sheet, the thickness of the first layer is 10 microns; the solid content ratio of the high-solid oily paint is more than 60%, add 2% of graphite, and mix them thoroughly; it can be rolled with heat, and the temperature of hot rolling is more than 40 degrees.

[0149] Step 3: Air-dry the coated metal sheet;

[0150] Step 4: Process the air-dried metal sheet into a box body;

[0151] Step 5: Remove the oxidation layer from the weld seams of the box;

[0152] Step 6: Two layers of powder spraying, first spray the base powder, then spray the flour powder; the base powder inside the box is 40 microns, which is epoxy powder; the base powder outside the box is 40 microns, which is epoxy powder; the flour outside the box is 45 microns, which is polyester powder, and the flour inside the box is 40 microns, which is epoxy powder;

[0153] Step 7: Solidify and cool.

[0154] The container metal sheet of the present invention can be a cold-rolled steel plate or a hot-rolled steel plate, and the protective coating system includes three layers, wherein the first layer, the primer layer is about 10 microns thick, and the thickness of the bottom layer reduces the high-solid oil-based paint; compared with the existing 35-micron primer layer, it greatly reduces the use of oil-based paint and can significantly reduce VOC emissions.

[0155] Optionally, the solid content ratio of the high-solid oil-based paint of the present invention is not less than 60%. The present invention adopts a solid content ratio of not less than 60%, which can greatly reduce VOC emissions compared to the existing solid content ratio of about 40%.

[0156] The zinc content of the present invention is zero; non-metallic conductive materials are used to replace the original zinc, which, on the one hand, utilizes the conductivity of non-metallic materials, and on the other hand, the non-metallic conductive materials themselves have less pollution. The non-metallic conductive materials can be graphite, etc. If graphite is used to replace the original zinc material, on the one hand, the conductivity can be guaranteed, and on the other hand, the corrosion resistance can be improved. In the present invention, the proportion of non-metallic conductive materials is between 0.5% and 10%, and the surface resistance of the primer layer is 10 2 Ohm to 10 9 In this example, the solid content is 70% and the non-metallic conductive material content is 5%.

[0157] The second layer is about 40 microns thick and is epoxy powder. It uses materials that meet FDA requirements. Since the thickness of the first layer is significantly less than the thickness of the existing first layer, in order to ensure the quality after coating, the thickness of the second layer is appropriately increased in the present invention, and its thickness is set to 40 microns;

[0158] The third layer is about 45 microns thick outside the box and is polyester powder; the thickness inside the box is about 40 microns and is epoxy powder; it meets FDA requirements; the present invention appropriately increases the spray thickness outside the box, thereby further ensuring the anti-corrosion effect after coating.

[0159] The powder coating of the present invention not only has excellent environmental performance, but also has all-round advantages in terms of process stability and coating quality compared with traditional coating processes.

[0160] Embodiment 2:

[0161] The steps of Example 2 are the same as those of Example 1, except that the thickness of the first coating layer is 10 microns, the thickness of the second layer is 43 microns, the thickness of the third layer is 43 microns inside the box and 46 microns outside the box.

[0162] Embodiment 3:

[0163] The steps of Example 3 are the same as those of Example 1, except that the thickness of the first coating layer is 12 microns, the thickness of the second layer is 41 microns, the thickness of the third layer is 41 microns inside the box and 44 microns outside the box.

[0164] Example 4

[0165] The protective coating in this embodiment is an 8 micron A1 layer, a 37 micron A2 layer and a 38 micron A3 layer.

[0166] Among them, the materials of the A1 layer include, by mass percentage: 25% isocyanate modified epoxy resin, 15% anti-rust pigment aluminum tripolyphosphate, 5% cyclohexanone, 10% xylene, 6% n-butanol, 8% curing agent modified polyamide, 10% non-metallic conductive material graphite, and 21% color filler titanium dioxide.

[0167] The epoxy powder of the A2 layer includes, by mass percentage, 50% polyester resin (acid value is 34mgKOH / g, viscosity is 3000mPa﹒s), 26% epoxy resin (epoxy value is 0.165eq / 100g, softening point is 87℃), 2% phenolic curing agent (969H06 phenolic curing agent produced by Daqing Qinglu Langrun Technology Co., Ltd.), 0.1% accelerator methyldiethanolamine, 0.5% leveling agent polyacrylic acid, 0.1% degassing agent diphenyl ethyl ketone, 5% composite filler silica and 0.2% toughening agent nano silica, and 16.1% pigment filler iron red.

[0168] The epoxy powder of the A3 layer includes, by mass percentage, 60% polyester resin (acid value of 34 mgKOH / g, viscosity of 3000 mPa.s), 20% epoxy resin (epoxy value of 0.165 eq / 100 g, softening point of 87°C), 1% leveling agent polyacrylic acid, 0.1% defoaming agent TEGO Foamex 825, 0.2% antioxidant B215 composite antioxidant, 0.5% toughening agent nano-silica, and 18.2% pigment filler phthalocyanine blue.

[0169] Example 5

[0170] The protective coating in this embodiment is a 12 micron A1 layer, a 43 micron A2 layer and a 43 micron A3 layer.

[0171] Among them, the materials of the A1 layer include, by mass percentage: 30% silicone acrylic modified epoxy resin, 10% anti-rust pigment zinc phosphate, 3% cyclohexanone, 8% xylene, 3% n-butanol, 20% curing agent polyamide 650 and 0.5% non-metallic conductive material graphene, and 25.5% color filler iron red.

[0172] The epoxy powder of the A2 layer includes, by mass percentage, 25% polyester resin (acid value of 34 mgKOH / g, viscosity of 6000 mPa.s), 45% epoxy resin (epoxy value of 0.160 eq / 100 g, softening point of 95°C), 10% phenolic curing agent (969H06 phenolic curing agent produced by Daqing Qinglu Langrun Technology Co., Ltd.), 2.4% accelerator aminophenol, 2% leveling agent acrylic polymer, 2% degassing agent stearic acid, 5% composite filler boron nitride and 2% toughening agent methyl methacrylate-butadiene-styrene terpolymer, and 6.6% pigment filler phthalocyanine blue.

[0173] The epoxy powder of the A3 layer includes, by mass percentage, 30% polyester resin (acid value 76 mgKOH / g, viscosity 6000 mPa﹒s), 36% epoxy resin (epoxy value 0.090 eq / 100 g, softening point 105°C), 1% leveling agent acrylic polymer, 1% defoaming agent BYK-028, 2% antioxidant β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 3% toughening agent dimethyl phthalate, and 27% color filler ultramarine.

[0174] Example 6

[0175] The protective coating in this embodiment is a 10 micron A1 layer, a 40 micron A2 layer and a 40 micron A3 layer.

[0176] Among them, the materials of the A1 layer include, by mass percentage: 28% dimer acid modified epoxy resin, 12% anti-rust pigment zinc oxide, 4% cyclohexanone, 9% xylene, 5% n-butanol, 15% curing agent isocyanate trimer and 5% non-metallic conductive material conductive mica, and 22% color filler permanent violet.

[0177] The epoxy powder of the A2 layer includes, by mass percentage, 30% polyester resin (acid value of 54 mgKOH / g, viscosity of 4500 mPa.s), 40% epoxy resin (epoxy value of 0.12 eq / 100g, softening point of 105°C), 5% phenolic curing agent (969H06 phenolic curing agent produced by Daqing Qinglu Langrun Technology Co., Ltd.), 1% accelerator 2,4,6-tris(dimethylaminomethyl)phenol, 1% leveling agent fluorine-modified acrylic acid, 0.5% deaerator diphenyl ethyl ketone, 0.5% deaerator stearic acid, 15% composite filler alumina, 1% toughening agent diethyl phthalate, and 6% pigment filler phthalocyanine blue.

[0178] The epoxy powder of the A3 layer includes, by mass percentage, 45% polyester resin (acid value of 54 mgKOH / g, viscosity of 4500 mPa.s), 30% epoxy resin (epoxy value of 0.110 eq / 100 g, softening point of 100°C), 0.5% leveling agent phosphate-modified acrylic acid, 0.5% defoaming agent BYK-024, 1% antioxidant 2,6-tert-butyl-4-methylphenol and 2% toughening agent dibutyl phthalate, and 21% color filler mica powder and ultramarine.

[0179] Example 7

[0180] The difference between this embodiment and embodiment 6 lies in the thickness of each layer, wherein the thickness of the A1 layer is 11 microns, the thickness of the A2 layer is 41 microns, and the thickness of the A3 layer is 41 microns.

[0181] Example 8

[0182] The protective coating in this embodiment is an A1 layer of 9 microns, an A2 layer of 38 microns and an A3 layer of 39 microns.

[0183] Among them, the materials of the A1 layer include, by mass percentage: 28% acrylic modified epoxy resin, 10% anti-rust pigment zinc molybdate, 3% cyclohexanone, 8% xylene, 3% n-butanol, 20% curing agent triethylenetetramine and 2.5% non-metallic conductive material graphene, and 25.5% color filler iron yellow.

[0184] The epoxy powder of the A2 layer includes, by mass percentage, 25% polyester resin (acid value of 76 mgKOH / g, viscosity of 6000 mPB﹒s), 45% epoxy resin (epoxy value of 0.090 eq / 100 g, softening point of 105°C), 3% phenolic curing agent (969H06 phenolic curing agent produced by Daqing Qinglu Langrun Technology Co., Ltd.), 2.4% accelerator imidazoline, 2% leveling agent acrylic polymer, 2% degassing agent stearic acid, 5% composite filler silica and 2% toughening agent methyl methacrylate-butadiene-styrene terpolymer, and 13.6% pigment filler phthalocyanine green.

[0185] The epoxy powder of the A3 layer includes, by mass percentage, 45% polyester resin (acid value of 54 mgKOH / g, viscosity of 4500 mPa.s), 30% epoxy resin (epoxy value of 0.110 eq / 100 g, softening point of 100°C), 0.5% leveling agent phosphate-modified acrylic acid, 0.5% defoaming agent BYK-022, 1% antioxidant 2,6-tributyl-4-methylphenol and 2% toughening agent tributyl phosphate, and 21% color filler mica powder and ultramarine.

[0186] Example 9

[0187] The protective coating in this embodiment is an 11 micron A1 layer, a 41 micron A2 layer and a 41 micron A3 layer.

[0188] Among them, the materials of the A1 layer include, by mass percentage: 25% of low-polymerization modified epoxy resin, 15% of anti-rust pigment alumina, 5% of cyclohexanone, 10% of xylene, 6% of n-butanol, 4% of curing agent isocyanate trimer, 4% of curing agent polyamide 650, 10% of non-metallic conductive material graphene, and 21% of color filler silicon powder.

[0189] The epoxy powder of the A2 layer includes, by mass percentage, 25% polyester resin (acid value of 76 mgKOH / g, viscosity of 3000 mPa.s), 22% epoxy resin (epoxy value of 0.165eq / 100g, softening point of 87°C), 1% phenolic curing agent (969H06 phenolic curing agent produced by Daqing Qinglu Langrun Technology Co., Ltd.), 0.1% accelerator colorless cobalt, 0.5% leveling agent polyacrylic acid, 0.1% degassing agent diphenyl ethyl ketone, 30% composite filler boron nitride and 0.2% toughening agent nano-silica, and 21.1% pigment filler iron red.

[0190] The epoxy powder of the A3 layer includes, by mass percentage, 39% polyester resin (acid value 60mgKOH / g, viscosity 5000mPa﹒s), 35% epoxy resin (epoxy value 0.120eq / 100g, softening point 100℃), 0.5% leveling agent phosphate modified acrylic acid, 0.5% defoaming agent TEGO-902W, 1% antioxidant 2,6-tert-butyl-4-methylphenol and 2% toughening agent dibutyl phthalate, and 23% color filler mica powder and ultramarine.

[0191] Example 10

[0192] The protective coating in this embodiment is a B1 layer of 8 microns, a B2 layer of 37 microns and a B3 layer of 44 microns.

[0193] Among them, the materials of the B1 layer include, by mass percentage: 25% isocyanate modified epoxy resin, 15% anti-rust pigment aluminum tripolyphosphate, 5% cyclohexanone, 10% xylene, 6% n-butanol, 8% curing agent modified polyamide, 10% non-metallic conductive material graphite, and 21% color filler titanium dioxide.

[0194] The epoxy powder of the B2 layer includes, by mass percentage, 50% polyester resin (acid value is 34mgKOH / g, viscosity is 3000mPa﹒s), 26% epoxy resin (epoxy value is 0.165eq / 100g, softening point is 87℃), 2% phenolic curing agent (969H06 phenolic curing agent produced by Daqing Qinglu Langrun Technology Co., Ltd.), 0.1% accelerator methyldiethanolamine, 0.5% leveling agent polyacrylic acid, 0.1% degassing agent diphenyl ethyl ketone, 5% composite filler silica and 0.2% toughening agent nano silica, and 16.1% pigment filler iron red.

[0195] The polyester powder of the B3 layer includes 30% high weather resistant polyester resin with an acid value of (32 mgKOH / g and a viscosity of 5000 mPa﹒s), 35% super weather resistant polyester resin with a hydroxyl value of (100 mgKOH / g and a viscosity of 3200 mPa﹒s), 2.3% curing agent TGIC, 24% curing agent B1400, 0.5% leveling agent polyether polyester modified organic siloxane, 0.1% accelerator methyl diethanolamine, 0.1% BYK-022 defoaming agent, 0.5% toughening agent dimethyl phthalate, 0.2% antioxidant 2,6-tert-butyl-4-methylphenol and 5% composite filler boron nitride, and 2.3% pigment filler phthalocyanine blue.

[0196] Embodiment 11

[0197] The protective coating in this embodiment is a 12 micron B1 layer, a 43 micron B2 layer and a 45 micron B3 layer.

[0198] The materials of the B1 layer include, by mass percentage, 30% of silicone acrylic modified epoxy resin, 10% of anti-rust pigment zinc phosphate, 3% of cyclohexanone, 8% of xylene, 3% of n-butanol, 20% of curing agent polyamide 650, 0.5% of non-metallic conductive material graphene, and 25.5% of pigment filler iron oxide red.

[0199] The epoxy powder of the B2 layer includes, by mass percentage, 25% polyester resin (acid value of 34 mgKOH / g, viscosity of 6000 mPa.s), 45% epoxy resin (epoxy value of 0.160 eq / 100 g, softening point of 95°C), 10% phenolic curing agent (969H06 phenolic curing agent produced by Daqing Qinglu Langrun Technology Co., Ltd.), 2.4% accelerator aminophenol, 2% leveling agent acrylic polymer, 2% degassing agent stearic acid, 5% composite filler boron nitride and 2% toughening agent methyl methacrylate-butadiene-styrene terpolymer, and 6.6% pigment filler phthalocyanine blue.

[0200] The polyester powder of the B3 layer includes 30% high weather resistant polyester resin with an acid value of 32 mgKOH / g and a viscosity of 5000 mPa﹒s, 35% super weather resistant polyester resin with a hydroxyl value of 110 mgKOH / g and a viscosity of 3800 mPa﹒s, 2.3% curing agent TGIC, 24% curing agent B1540, 0.5% leveling agent polyether polyester modified organic siloxane, 0.1% accelerator methyl diethanolamine, 0.1% BYK-022 defoaming agent, 0.5% toughening agent dimethyl phthalate, 0.2% antioxidant 2,6-tert-butyl-4-methylphenol and 3% composite filler silica, 4.3% pigment filler phthalocyanine blue.

[0201] Example 12

[0202] The protective coating in this embodiment is a 12 micron B1 layer, a 43 micron B2 layer and a 46 micron B3 layer.

[0203] Among them, the materials of the B1 layer include, by mass percentage: 30% of silicone acrylic modified epoxy resin, 10% of anti-rust pigment aluminum tripolyphosphate, 3% of cyclohexanone, 8% of xylene, 3% of n-butanol, 20% of curing agent polyamide 650 and 0.5% of non-metallic conductive material graphene, and 25.5% of color filler iron red.

[0204] The epoxy powder of the B2 layer includes, by mass percentage, 25% polyester resin (acid value of 76 mgKOH / g, viscosity of 6000 mPB﹒s), 45% epoxy resin (epoxy value of 0.090 eq / 100g, softening point of 105°C), 3% phenolic curing agent (969H06 phenolic curing agent produced by Daqing Qinglu Langrun Technology Co., Ltd.), 2.4% accelerator imidazoline, 2% leveling agent acrylic polymer, 2% degassing agent stearic acid, 5% composite filler silica and 2% toughening agent methyl methacrylate-butadiene-styrene terpolymer, and 13.6% pigment filler phthalocyanine green.

[0205] The polyester powder of the B3 layer includes 45% of high weather-resistant polyester resin with an acid value of (29 mgKOH / g and a viscosity of 4500 mPa﹒s), 22% of super weather-resistant polyester resin with a hydroxyl value of (120 mgKOH / g and a viscosity of 4200 mPa﹒s), 2.7% of curing agent TGIC, 0.5% of curing agent HAA, 14% of curing agent B1320, 1.5% of leveling agent polyether polyester modified organic siloxane, 0.1% of accelerator methyl diethanolamine, 0.1% of defoaming agent TEGO-902W, 0.5% of toughening agent tributyl phosphate, 0.2% of BASF antioxidant 1010 and 11% of composite filler boron nitride, and 2.9% of pigment filler phthalocyanine blue.

[0206] Embodiment 13

[0207] The protective coating in this embodiment is a 10 micron B1 layer, a 40 micron B2 layer and a 45 micron B3 layer.

[0208] Among them, the materials of the B1 layer include, by mass percentage: 28% dimer acid modified epoxy resin, 12% anti-rust pigment zinc oxide, 4% cyclohexanone, 9% xylene, 5% n-butanol, 15% curing agent isocyanate trimer and 5% non-metallic conductive material conductive mica, and 22% color filler permanent violet.

[0209] The epoxy powder of the B2 layer includes, by mass percentage, 30% polyester resin (acid value of 70 mgKOH / g, viscosity of 4500 mPB﹒s), 40% epoxy resin (epoxy value of 0.120 eq / 100g, softening point of 102°C), 3% phenolic curing agent (969H06 phenolic curing agent produced by Daqing Qinglu Langrun Technology Co., Ltd.), 1% accelerator 2,4,6-tris(dimethylaminomethyl)phenol, 1% leveling agent fluorine-modified acrylic acid, 0.5% deaerator dibenzoyl ketone, 0.5% deaerator stearic acid, 15% composite filler alumina, 1% toughening agent diethyl phthalate, and 6% pigment filler phthalocyanine blue.

[0210] The polyester powder of the B3 layer includes 38% of high weather-resistant polyester resin with an acid value of (34 mgKOH / g and a viscosity of 6000 mPa﹒s), 25% of super weather-resistant polyester resin with a hydroxyl value of (111 mgKOH / g and a viscosity of 3600 mPa﹒s), 2.5% of curing agent HAA, 15% of curing agent B1400, 0.5% of leveling agent polyether polyester modified organic siloxane, 3% of accelerator, 1% of defoaming agent polydimethylsiloxane, 3.2% of toughening agent triethyl phosphate, 2% of antioxidant bis (3,5-tertiary butyl-4-hydroxyphenyl) sulfide and 6% of composite filler mica powder, and 4.3% of color filler phthalocyanine blue.

[0211] Embodiment 14

[0212] The difference between this embodiment and embodiment 13 lies in the thickness of each layer, wherein the thickness of the B1 layer is 11 microns, the thickness of the B2 layer is 41 microns, and the thickness of the B3 layer is 41 microns.

[0213] Embodiment 15

[0214] The protective coating in this embodiment is a B1 layer of 8 microns, a B2 layer of 37 microns and a B3 layer of 44 microns.

[0215] Among them, the materials of the B1 layer include, by mass percentage: 25% of low-polymerization modified epoxy resin, 15% of anti-rust pigment alumina, 5% of cyclohexanone, 10% of xylene, 6% of n-butanol, 4% of curing agent isocyanate trimer, 4% of curing agent polyamide 650, 10% of non-metallic conductive material graphene, and 21% of color filler silicon powder.

[0216] The epoxy powder of the B2 layer includes, by mass percentage, 25% polyester resin (acid value is 38mgKOH / g, viscosity is 3000mPa﹒s), 22% epoxy resin (epoxy value is 0.165eq / 100g, softening point is 87℃), 1% phenolic curing agent (969H06 phenolic curing agent produced by Daqing Qinglu Langrun Technology Co., Ltd.), 0.1% accelerator methyldiethanolamine, 0.5% leveling agent polyacrylic acid, 0.1% degassing agent diphenyl ethyl ketone, 30% composite filler boron nitride and 0.2% toughening agent nano-silica, and 21.1% pigment filler iron red.

[0217] The polyester powder of the B3 layer includes 30% high weather resistant polyester resin with an acid value of (32 mgKOH / g and a viscosity of 5000 mPa﹒s), 22% super weather resistant polyester resin with a hydroxyl value of (100 mgKOH / g and a viscosity of 3200 mPa﹒s), 3.5% curing agent TGIC, 14% curing agent B1400, 0.5% leveling agent polyether polyester modified organic siloxane, 0.1% accelerator methyl diethanolamine, 0.1% BYK-022 defoaming agent, 0.5% toughening agent dimethyl phthalate, 0.2% antioxidant 2,6-tert-butyl-4-methylphenol and 25% composite filler boron nitride, 4.1% pigment filler phthalocyanine blue.

[0218] Comparative Example 1:

[0219] First, the surface of the metal sheet is degreased, cleaned, dried, shot blasted, and pre-coated with a 35-micron zinc-rich primer. After the pre-treatment is completed, it will enter cold processing (punching, shearing, and pressing), steel structure assembly welding, and the welds will be shot blasted before the whole box is painted; the second layer is sprayed with a 35-micron intermediate paint, and the third layer is sprayed with a 40-micron topcoat.

[0220] Comparative Example 2

[0221] The protective coating is a 10 micron B1 layer, a 40 micron B2 layer and a 40 micron B3 layer.

[0222] The B1 layer is an oil-based epoxy zinc-rich primer (DWB ZINC 30 produced by Jiangsu DWB Coatings Co., Ltd.

[0223] The epoxy powder of the B2 layer includes, by mass percentage, 30% polyester resin (acid value of 70 mgKOH / g, viscosity of 4500 mPB﹒s), 40% epoxy resin (epoxy value of 0.120 eq / 100g, softening point of 102°C), 3% phenolic curing agent (969H06 phenolic curing agent produced by Daqing Qinglu Langrun Technology Co., Ltd.), 1% accelerator 2,4,6-tris(dimethylaminomethyl)phenol, 1% leveling agent fluorine-modified acrylic acid, 0.5% deaerator dibenzoyl ketone, 0.5% deaerator stearic acid, 15% composite filler alumina, 1% toughening agent diethyl phthalate, and 6% pigment filler phthalocyanine blue.

[0224] The polyester powder of the B3 layer includes 45% of high weather-resistant polyester resin with an acid value of (29 mgKOH / g and a viscosity of 4500 mPa﹒s), 22% of super weather-resistant polyester resin with a hydroxyl value of (120 mgKOH / g and a viscosity of 4200 mPa﹒s), 3.5% of curing agent TGIC, 14% of curing agent B1400, 1.5% of leveling agent polyether polyester modified organic siloxane, 0.1% of accelerator methyl diethanolamine, 0.1% of defoaming agent TEGO-902W, 0.5% of toughening agent tributyl phosphate, 0.2% of BASF antioxidant 1010 and 11% of composite filler boron nitride, and 2.6% of pigment filler phthalocyanine blue.

[0225] Comparative Example 3

[0226] The protective coating is a 10 micron A1 layer, a 40 micron A2 layer and a 40 micron A3 layer.

[0227] The A1 layer is an oil-based epoxy zinc-rich primer (DWB ZINC 30 produced by Jiangsu DWB Coatings Co., Ltd.

[0228] The epoxy powder of the A2 layer includes, by mass percentage, 30% polyester resin (acid value of 70 mgKOH / g, viscosity of 4500 mPa.s), 40% epoxy resin (epoxy value of 0.120 eq / 100g, softening point of 102°C), 3% phenolic curing agent, 1% accelerator 2,4,6-tris(dimethylaminomethyl)phenol, 1% leveling agent fluorine-modified acrylic acid, 0.5% degassing agent dibenzoyl ketone, 0.5% degassing agent stearic acid, 15% composite filler alumina, 1% toughening agent diethyl phthalate, and 6% pigment filler phthalocyanine blue.

[0229] The epoxy powder of the A3 layer includes, by mass percentage, 45% polyester resin (acid value of 54 mgKOH / g, viscosity of 4500 mPa.s), 30% epoxy resin (epoxy value of 0.110 eq / 100 g, softening point of 100°C), 0.5% leveling agent phosphate-modified acrylic acid, 0.5% defoaming agent BYK-024, 1% antioxidant 2,6-tert-butyl-4-methylphenol and 2% toughening agent dibutyl phthalate, and 21% color filler mica powder and ultramarine.

[0230] Comparative Example 4

[0231] First, the surface of the metal sheet is degreased, cleaned, dried, shot blasted, and pre-coated with a 10-micron zinc-rich primer. After the pre-treatment is completed, it will enter cold processing (punching, shearing, and pressing), steel structure assembly welding, and the welds will be shot blasted before the whole box is painted; the second layer is sprayed with a 20-micron intermediate water-based epoxy zinc-rich paint, and the third layer is sprayed with a 50-micron topcoat.

[0232] Among them, the zinc-rich primer uses DWep ZINC 500 produced by Jiangsu Dwep Paint Co., Ltd.

[0233] The intermediate water-based epoxy zinc-rich paint adopts DWB AC PRIMER produced by Jiangsu Derwei Paint Co., Ltd.

[0234] The topcoat is DWB AC INTERI0R from Jiangsu Derwei Paint Co., Ltd.

[0235] Comparative Example 5

[0236] First, the surface of the metal sheet is degreased, cleaned, dried, shot blasted, and pre-coated with a 10-micron zinc-rich primer. After the pre-treatment is completed, it will enter cold processing (punching, shearing, and pressing), steel structure assembly welding, and the welds will be shot blasted before the whole box is painted; the second layer is sprayed with a 20-micron intermediate water-based epoxy zinc-rich paint, the third layer is sprayed with a 50-micron intermediate paint, and the fourth layer is sprayed with a 40um polyurethane topcoat.

[0237] Among them, the zinc-rich primer uses DWep ZINC 500 produced by Jiangsu Dwep Paint Co., Ltd.

[0238] The intermediate water-based epoxy zinc-rich paint adopts DWB AC PRIMER produced by Jiangsu Derwei Paint Co., Ltd.

[0239] The intermediate paint is DWB AC PRIMER produced by Jiangsu Derwei Paint Co., Ltd. The polyurethane topcoat is DWpu FINISH 20 produced by Jiangsu Derwei Paint Co., Ltd.

[0240] Test method and results:

[0241] The samples produced by the construction processes of the embodiment and the comparative example were tested for corrosion expansion performance: the specific test method is:

[0242] Cold-rolled steel plates of the same material, thickness and size are used, and the construction processes in Example 1, Example 2, Example 3 and the comparative example are respectively adopted to produce Sample 1, Sample 2, Sample 3 and Sample 4.

[0243] Cold-rolled steel plates of the same material, thickness and size were used, and the protective coatings of Examples 4 to 15 and the protective coatings of Comparative Examples 2 to 5 were respectively used to make samples under the same conditions using the construction process in this application.

[0244] The same T-shaped line is made on sample 1, sample 2, sample 3 and sample 4. The specific method of making the T-shaped line is as follows:

[0245] Draw a T-shaped line on the sample, and use a blade to draw a line to the bottom. The lengths of the T-shaped line are 50mm and 76mm respectively.

[0246] The same T-shaped lines were made on the samples of Examples 4 to 15 and Comparative Examples 2 to 5. The specific method of making the T-shaped lines is as follows:

[0247] Draw a T-shaped line on the sample, and use a blade to draw a line to the bottom. The lengths of the T-shaped line are 50mm and 76mm respectively.

[0248] Samples 1, 2, 3 and 4 were placed in the same salt spray test chamber at the same time and taken out after 1000 hours. In the test chamber: the concentration of the precipitation salt solution was 5% sodium chloride solution by mass, the test chamber temperature was (35±2)℃, and the pH value of the precipitation salt solution was 6.5~7.2 (25℃).

[0249] The samples of Examples 4 to 15 and Comparative Examples 2 to 5 were simultaneously placed in the same salt spray test chamber and taken out after 1000 hours. In the test chamber: the concentration of the precipitation salt solution was 5% sodium chloride solution by mass, the test chamber temperature was (35±2)°C, and the pH value of the precipitation salt solution was 6.5 to 7.2 (25°C).

[0250] The results are as follows Figure 1-4 As shown, after measurement, the corrosion expansion performance test results are shown in Table 1, where the corrosion width is the average width.

[0251] Table 1

[0252]

[0253]

[0254] It can be seen from the test results that the corrosion resistance of the present invention is significantly better than that of the existing technology, among which the corrosion width of sample 4 is more than 1.8 times that of sample 3. And from the overall corrosion effect of the sample, the corrosion of sample 4 is significantly higher than that of the present invention. That is, not only is the thickness of the present invention significantly lower than the spraying thickness in the prior art, but its corrosion resistance is also significantly better than that of the prior art. In particular, its corrosion resistance is significantly better than that of the prior art.

[0255] The corrosion width of Examples 4 to 15 is significantly smaller than that of Comparative Examples 2 to 5. Therefore, the corrosion resistance of Examples 4 to 15 is significantly better than that of the prior art.

[0256] Combination Figures 5 to 7 as well as Fig.11 It is obvious that the corrosion of Comparative Example 2 is more serious. Figures 8 to 10 as well as Fig.12 It is obvious that the corrosion of 3 is more serious. Therefore, the use of the zinc-free primer in this application can avoid the influence of zinc on the accelerated corrosion expansion and ensure the anti-corrosion performance of the entire protective coating.

[0257] Anti-corrosion performance is a very important parameter in shipping containers. Shipping containers are transported in the sea under harsh natural conditions. Due to the waves, the containers often rub and collide with each other, which easily causes partial wear of the containers. Therefore, there are extremely high requirements for anti-corrosion performance. The present invention not only uses less materials, but also has significantly better anti-corrosion performance than existing products. In addition, the construction process of the present invention avoids the discharge of sewage and reduces the emission of VOC, and has a good environmental protection effect.

[0258] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that changes may be made to the embodiments and combinations of elements may be made without departing from the principles and spirit of the invention, the scope of the invention being defined by the appended claims and their equivalents.

Claims

1. A powder protective coating for a shipping container, characterized in that: The container includes an inner surface of the container and an outer surface of the container; At least part of the container is made of metal sheet; in: The metal sheet forming the inner surface of the container includes at least three layers of coating structure: A1 layer, A2 layer, and A3 layer. The material of A1 layer includes: high-solid oil-based paint, non-metallic conductive material; A1 layer does not contain metal zinc; the material of A2 layer is epoxy powder; the material of A3 layer is epoxy powder; And / or, the metal sheet forming the outside of the container comprises at least: a three-layer coating structure of B1 layer, B2 layer, and B3 layer; the material of B1 layer comprises: high-solid oil-based paint, non-metallic conductive material; B1 layer does not contain metallic zinc; the material of B2 layer is epoxy powder; the material of B3 layer is polyester powder.

2. The protective coating according to claim 1, characterized in that: The A1 layer is formed by roller coating before the metal sheet is formed into a container; the A2 and A3 layers are formed by spray coating after the container body is formed; And / or, the B1 layer is formed by roller coating before the metal sheet is formed into a container; and the B2 and B3 layers are formed by spray coating after the container body is formed.

3. The protective coating according to claim 1, characterized in that: in, The thickness of the A1 layer is smaller than that of the A2 and A3 layers; And / or, the thickness of the B1 layer is smaller than the thickness of the B2 and B3 layers.

4. The protective coating according to claim 1, characterized in that: The solid content of the high-solid oily paint in the A1 layer is not less than 60%, and the content of the non-metallic conductive material ranges from 0.5% to 10% of the weight of the high-solid oily paint; And / or, the solid content of the high-solid oily paint in the B1 layer is not less than 60%, and the content of the non-metallic conductive material is in the range of 0.5%-10% of the weight of the high-solid oily paint.

5. The protective coating according to claim 1, characterized in that: The thickness of the A1 layer is 8-12 microns, the thickness of the A2 layer is 37-43 microns, and the thickness of the A3 layer is 38-43 microns; And / or, the thickness of the B1 layer is 8-12 microns, the thickness of the B2 layer is 37-43 microns, and the thickness of the B3 layer is 44-46 microns.

6. The protective coating according to claim 1, characterized in that: The non-metallic conductive material in the A1 and B1 layers is graphite, and the content of graphite is approximately 2%.

7. The protective coating according to claim 1, characterized in that: The solid content ratio of the high-solid oily paint in the A1 and B1 layers is 70%, and the content of the non-metallic conductive material is in the range of 5% of the weight of the high-solid oily paint.

8. The protective coating according to claim 1, characterized in that: The materials forming the A1 layer and the B1 layer include, by mass percentage, 25-30% of modified epoxy resin, 10-15% of anti-rust pigment, 3-5% of cyclohexanone, 8-10% of xylene, 3-6% of n-butanol, 8-20% of curing agent, and 0.5-10% of non-metallic conductive material, and the rest are pigments and fillers.

9. The protective coating according to claim 8, characterized in that The non-metallic conductive material includes at least one of graphite, graphene and conductive mica.

10. The protective coating according to claim 1, characterized in that According to mass percentage, the epoxy powders of A2 and B2 include: 25-50% polyester resin, 22-45% epoxy resin, 1-10% phenolic curing agent, 0.1-2.4% accelerator, 0.5-2% leveling agent, 0.1-2% deaerator, 5-30% composite filler and 0.2-2% toughening agent, and the rest are pigments and fillers.

11. The protective coating according to claim 10, characterized in that The polyester resin has an acid value of 34 to 76 mgKOH / g and a viscosity of 3000 to 6000 mPa.s; and / or, The epoxy value of the epoxy resin is 0.090-0.165 eq / 100 g, and the softening point is 87-105° C.

12. The protective coating according to claim 1, characterized in that According to mass percentage, the epoxy powder A3 includes 30-60% polyester resin, 20-36% epoxy resin, 0.5-1% leveling agent, 0.1-1% defoaming agent, 0.2-2% antioxidant and 0.5-3% toughening agent, and the rest is pigment and filler.

13. The protective coating according to claim 12, characterized in that The polyester resin has an acid value of 34 to 76 mgKOH / g and a viscosity of 3000 to 6000 mPa.s; and / or, The epoxy value of the epoxy resin is 0.090-0.165 eq / 100 g, and the softening point is 87-105° C.

14. The protective coating according to claim 1, characterized in that According to mass percentage, the B3 polyester powder includes 30-45% of high weather-resistant polyester resin, 22-35% of super weather-resistant polyester resin, 0-3.5% of triglycidyl isocyanurate, 0-2.5% of hydroxyalkylamide, 14-24% of blocked polyisocyanate, 0.5-1.5% of leveling agent, 0.1-3% of accelerator, 0.1-1% of defoamer, 0.5-3.2% of toughening agent, 0.2-2% of antioxidant and 2-25% of composite filler, and the rest is color filler.

15. The protective coating according to claim 14, characterized in that The acid value of the highly weather-resistant polyester is 29-34 mgKOH / g, and the viscosity is 4500-6000 mPa﹒ s; The super weather-resistant polyester has a hydroxyl value of 100-120 mgKOH / g and a viscosity of 3200-4200 mPa﹒s.

16. A construction process for a protective coating of a container according to any one of claims 1 to 15, characterized in that: The steps include: Derusting and / or sanding metal sheets; With hot coating, the coating or the plate is heated before coating the A1 layer and the B1 layer; Drying or air drying, wherein the air drying uses hot air; Processing and welding metal sheets to form a box; Sandblast the welds of the entire box; A2 layer and B2 layer are sprayed; A3 layer and B3 layer are sprayed; Solidify and cool.

17. The construction process according to claim 16, characterized in that: When hot air is used for air drying, the temperature of plates thicker than 4 mm after hot air heating shall not be lower than 85°C.

18. A shipping container, characterized in that: The protective coating comprises any one of claims 1 to 15; or, the construction process comprises any one of claims 16 to 17.

19. A zinc-free primer for a container, characterized in that: According to the mass percentage, it includes: 25-30% of modified epoxy resin, 10-15% of anti-rust pigment, 3-5% of cyclohexanone, 8-10% of xylene, 3-6% of n-butanol, 8-20% of curing agent, and 0.5-10% of non-metallic conductive material, and the rest is color filler.

20. The zinc-free primer according to claim 19, characterized in that: The non-metallic conductive material includes at least one of graphite, graphene and conductive mica.